1993
DOI: 10.1136/jnnp.56.5.526
|View full text |Cite
|
Sign up to set email alerts
|

The use of botulinum toxin in the treatment of adductor spasmodic dysphonia.

Abstract: Botulinum toxin injections have been used to treat 31 patients with adductor spasmodic dysphonia. Injections of 300-3 75 units of botulinum toxin were performed bilaterally into the thyroarytenoid muscle. This treatment significantly decreased the standard deviation of the fundamental frequency of the speech sample, indicating a reduction in the variability of pitch amongst patients. A total of 96% of patients' subjective diary reports showed an improvement with a median of 7 days to peak effect and a 5 week d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 20 publications
1
30
0
3
Order By: Relevance
“…Early studies of connected speech were of limited scope. For example, Ford, Bless and Patel [14] demonstrated decreased oral reading time from pre-to-post treatment, whereas Whurr et al [15] observed reduced standard deviation of f 0 following treatment. A major reason for such limited analyses is that periodicity-based signal processing algorithms used to measure jitter, shimmer, or signal-to-noise ratio (SNR), may be inappropriate for the analysis and characterization of connected speech for severely disordered voices [12,16].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of connected speech were of limited scope. For example, Ford, Bless and Patel [14] demonstrated decreased oral reading time from pre-to-post treatment, whereas Whurr et al [15] observed reduced standard deviation of f 0 following treatment. A major reason for such limited analyses is that periodicity-based signal processing algorithms used to measure jitter, shimmer, or signal-to-noise ratio (SNR), may be inappropriate for the analysis and characterization of connected speech for severely disordered voices [12,16].…”
Section: Introductionmentioning
confidence: 99%
“…The aims of this perceptual analysis are 1) to verify the discrepant characteristics of the French description of SD speech in the study by Klap and colleagues highlighted above, 2) to describe and illustrate the phonetic features of SD in these French speakers using criteria developed in the characterisation of the vocal impairment in English (Whurr et al, 1993;Whurr and Moore, 1996) and 3) to compare and contrast the findings for these French speaking subjects with the present characterisation of SD in English speakers (Ludlow et al, 1988).…”
Section: (Translated By Ml)]mentioning
confidence: 92%
“…An analysis that separates these two categories is given below in Table 3.) Interestingly, this feature is typically associated in the literature on English SD speakers as an early post-injection side effect of BTX, which weakens the adductor muscles of the larynx (Blitzer et al, 1988;Whurr et al, 1993;). In the present group of French SD speakers, breathiness was found in all cases, although 2 had never been injected with BTX and 3 other treated subjects were beyond the period of time in which these physiological side effects are expected to occur.…”
Section: Analysis 1: Perception Of Severity and Distribution Of Pathomentioning
confidence: 97%
See 2 more Smart Citations